Análisis del proceso contable de la Escuela de Educación Básica Mahatma Gandhi - Campoverde Valencia, Gilda Trinidad (2021)
The management of accounting processes within a company has become a substantial part and of pressing importance for a correct commercial management in companies today, the interruption or mismanagement of these with certainty negatively influences the commercial health of Any entity, the impact of these attributions will have a notable firmness mark in the financial statements, and these in turn will determine the position to be adopted for the control and correction of those accounting processes that are outside the growth objectives and affect cooperative interests. This is the origin of the present investigation called ANALYSIS OF THE ACCOUNTING PROCESS OF THE MAHATMA GANDHI BASIC EDUCATION SCHOOL, which aims to analyze its accounting processes, being able to show that there is an outdated regulation for the management of accounting processes in the company and it has a negative impact on the financial statements, due to the fact that it is making use of outdated and not duly recorded information, which causes its accounting staff to take improvised actions to handle problematic situations. It is worth mentioning that this case study was developed through a qualitative and descriptive research approach where each of the staff members of the administrative and accounting area was interviewed, obtaining a favorable response to the interview carried out.